A new species of Postia (Basidiomycota) based on morphological and molecular characteristics - Yuan, Hai-Sheng; Mu, Yan-Hong; Qin, Wen-Min (Phytotaxa, 2017)
A new wood-decaying polypore from southern China, Postia cylindrica, is described and illustrated using morphological characteristics and rDNA ITS sequences. The new species is characterized by resupinate to effused reflexed basidiocarps, cream to buff and azonate pileal surface, reddish-brown and incurved margin, gloeoplerous hyphal cells in cuticular layer, absence of cystidia, and cylindrical, thin-walled basidiospores. Molecular analyses confirm the phylogenetic position of the new species Postia. The discriminating characters of the new species and the closely related species are discussed.